2021
DOI: 10.1007/s40171-021-00281-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Traceability System and Managerial Initiative on Indonesian Food Cold Chain Performance: A Covid-19 Pandemic Perspective

Abstract: This study aims to determine the effect of managerial initiatives on the adoption of traceability systems on food cold chain performance during the Covid-19 pandemic. Managerial initiatives are allegedly needed to improve the company's performance because it improves the traceability system in the supply chain. In addition, the effect of the traceability system adoption on the Indonesian food cold-chain performance during the Covid-19 pandemic is also discussed in this study. This study uses a quantitative app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 118 publications
0
27
0
3
Order By: Relevance
“…Blockchain traceability technology is a fast-growing business that can respond quickly to needs across the country and the world, such as new crown virus traceability [ 103 ] and cold chain traceability [ 104 ]. Yet blockchain traceability is affected by a combination of environmental, political, and religious factors, which will be the biggest threat they face [ 105 ].…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…Blockchain traceability technology is a fast-growing business that can respond quickly to needs across the country and the world, such as new crown virus traceability [ 103 ] and cold chain traceability [ 104 ]. Yet blockchain traceability is affected by a combination of environmental, political, and religious factors, which will be the biggest threat they face [ 105 ].…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…Masudin et al [61] demonstrated that implementing green supply chain management practices has positive and significant impacts on performance. Managerial initiatives have been found to support traceability system adoption, which significantly and positively affects food cold chain performance [62]. Consequently, the investigation of blockchain implementation for supporting ecologically embedded coffee supply chains in this research is justified.…”
Section: Blockchain Impacts On Business Performancementioning
confidence: 92%
“…It has greater importance in the business because businesses are designed to provide the products to the consumers at the appropriate delivery time to satisfy the consumers. Indeed, according to the study of Masudin, Ramadhani, Restuputri, and Amallynda (2021), the consumers seek the information about their shipment because they want to track the time and location of delivery, in this regard, the role of e-traceability is increased because to satisfy this need of customers, businesses are required to develop a professional e-traceability system with well-trained staff. Also, if the e-traceability has quality in providing services to the consumers then their behavior changed to a higher level of satisfaction (Corallo et al, 2019;Lee & Yeon, 2021).…”
Section: 3mentioning
confidence: 99%